Changes in endolymphatic hydrops in patients with Ménière's disease treated conservatively for more than 1 year. (September 2015) - Suga, Kenji; Kato, Masahiro; Yoshida, Tadao; Nishio, Naoki; Nakada, Takafumi; Sugiura, Saiko; Otake, Hironao; Kato, Ken; Teranishi, Masaaki; Sone, Michihiko; Naganawa, Shinji; Nakashima, Tsutomu
Abstract Conclusion: This study revealed that endolymphatic hydrops (EH) reduced in some cases with Ménière's disease (MD) treated conservatively. It appears that the EH reduction was associated with improvement of the clinical symptoms. Objectives: The relationship between the degree of EH and clinical symptoms is not clear at present. The purpose of the present study was to investigate the time course of the relationship in patients with MD treated conservatively. Patients: Twelve patients with MD treated conservatively for more than 1 year in a university hospital. Methods: Twenty ears of 12 patients with MD treated conservatively were evaluated. The presence or absence of vertigo, tinnitus and ear fullness was confirmed when magnetic resonance imaging (MRI) was performed. Using a 3 T MRI scanner, three-dimensional fluid-attenuated inversion recovery (3D-FLAIR) MRI was performed 2 or 3 times 24 hours after intra-tympanic gadolinium injection or 4 hours after intravenous gadolinium injection. Results: In the three ears in which the symptoms alleviated, EH was reduced in two ears, but EH was reduced in only one of 17 ears in which the symptoms did not alleviate. The Fisher exact test revealed that EH reduction occurred more frequently in ears with alleviation of the symptoms (p < 0.05).